Managerial Networking and Frugal Innovation: Situational Leadership Perspective - Xuecheng, Wei; Iqbal, Qaisar (Frontiers in Psychology, 2022)
This study aimed to examine the integrated relationships of business ties, political ties, sustainable leadership, and frugal innovation. The correlation was assessed with the consideration of social network and situational leadership theories. Data was collected from 363 Small and Medium Enterprises (SMEs) employees in Pakistan with a response rate of 72.60%. Accordingly, the Partial Least Squares-Structural Equation Modelling (PLS-SEM) was employed to examine the validity of the proposed hypotheses. Empirical findings confirmed the significant impact of managerial and business ties on frugal innovation, strengthened by sustainable leadership. However, data analysis negated the positive impact of political ties on frugal innovation, which remains non-significant with the introduction of sustainable leadership among Pakistani SMEs. Hence, future studies are recommended to explore other conditional factors and mediating mechanisms in the relationship between managerial ties and frugal innovation. This idea can bring a deeper insight into the vital role of networking. To the best of the author’s knowledge, no prior study is available about the integrated relationships of managerial ties, frugal innovation, and sustainable leadership. This study enriches the literature in innovation management, especially concerning the social network and situational leadership model.